2016
DOI: 10.1159/000442878
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Moderate Hypoglycemia Suppresses Brain-Derived Neurotrophic Factor Expression in the Prefrontal Cortex and Impairs Sensorimotor Gating in the Posthypoglycemic Period in Young Rats

Abstract: Recurrent hypoglycemia is common in infants and children. In developing rat models, recurrent moderate hypoglycemia leads to neuronal injury in the medial prefrontal cortex. To understand the effects beyond neuronal injury, 3-week-old male rats were subjected to 5 episodes of moderate hypoglycemia (blood glucose concentration, approx. 30 mg/dl for 90 min) once daily from postnatal day 24 to 28. Neuronal injury was determined using Fluoro-Jade B histochemistry on postnatal day 29. The effects on brain-derived n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…It is well known that glucose reperfusion plays a major role in neuronal death, mainly when blood glucose exceeds physiological levels resulting in hyperglycemia. 40,50,51 Previous data have reported a decrease in GSH content even after a single episode of moderate hypoglycemia, 52 and some studies have shown that RH in healthy animals produces an increase in LPO and 4-HNE immunoreactivity, without leading to significant neuronal death or cognitive decline. 13,19,25 Furthermore, studies have reported that RH in healthy animals can even improve cognitive performance due to synaptic changes and brain metabolic adaptations.…”
Section: Discussionmentioning
confidence: 98%
“…It is well known that glucose reperfusion plays a major role in neuronal death, mainly when blood glucose exceeds physiological levels resulting in hyperglycemia. 40,50,51 Previous data have reported a decrease in GSH content even after a single episode of moderate hypoglycemia, 52 and some studies have shown that RH in healthy animals produces an increase in LPO and 4-HNE immunoreactivity, without leading to significant neuronal death or cognitive decline. 13,19,25 Furthermore, studies have reported that RH in healthy animals can even improve cognitive performance due to synaptic changes and brain metabolic adaptations.…”
Section: Discussionmentioning
confidence: 98%
“…[ 2 ] Early manifestations of neonatal hypoglycemia may be asymptomatic or present as mild diaphoresis, lethargy, feeding difficulties, and decreased responsiveness, often lacking typical symptoms, thereby posing challenges for timely clinical detection. [ 3 ] Given that the energy supply to the neonatal brain primarily relies on glucose, persistent or recurrent episodes of hypoglycemia can profoundly disrupt neurological development, with severe cases even posing life-threatening risks. [ 4 ] Consequently, effective prevention and management of neonatal hypoglycemia hold paramount importance in ensuring healthy developmental outcomes for newborns.…”
Section: Introductionmentioning
confidence: 99%